Enhancing Usefulness and Usability of a Clinical Decision Support Prototype for Antibiotic Stewardship. Issue 1 (September 2020) - Patterson, Emily S.; DiLoreto, Giavanna N.; Vanam, Rohith; Hade, Erinn; Hebert, Courtney
Human factors engineering can enhance software usefulness and usability. We describe a multi-method approach to improve clinical decision support (CDS) for antibiotic stewardship. We employed a heuristic review to generate recommendations to improve the usability of a prototype CDS to support empiric antibiotic prescribing in the hospital setting. We then engaged in a design improvement cycle in collaboration with software programmers, which resulted in additional enhancements to our prototype. Finally, we used the revised prototype during three walkthrough demonstration interviews with physician and pharmacist subject matter experts. These walkthrough interviews generated recommendations to improve the interface, functionality, and tailoring for groups of users. We discuss common elements of the recommendations for models for using clinical decision support in general.